AMBIVALENCES OF A “TOUR DE FORCE: ISTORIA LITERATURII ROMÂNE CONTEMPORANE” AS CRITIQUE AND AS LITERATURE - MATEI, Alexandru (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Ambivalences of a Tour de Force: Istoria Literaturii Române Contemporane as Critique and as Literature. This essay starts from hypothesizing a double dimension of Mihai Iovănel’s History: critical and literary (or, as Matei says, poetic). The idea of such an interpretation is given by Iovănel’s quoting a late text by Louis Althusser, in which the French philosopher defines the figure of an “aleatory materialist,” as opposed to a “dialectical” materialist. While critics have already discussed the critical dimension of Iovănel’s project, an aspect Matei also examines in the last part of his contribution, less has been said, he maintains, about the History as a literary project, as “writing.” Matei thus attends to the qualities and shortcomings of Iovănel’s project, which stem, he claims, from the aforementioned double dimension of the History. Article history: Received 20 February 2022; Revised 19 August 2022; Accepted 31 August 2022; Available online 20 September 2022; Available print 30 September 2022. REZUMAT. Ambivalențele unui tour de force: Istoria literaturii române contemporane, proiect critic și proiect literar. Eseul de față pornește de la ipoteza că Istoria literaturii române contemporane a lui Mihai Iovănel are o dublă dimensiune: una critică și una literară (poetică). Ideea unei astfel de interpretări își are originea într-un citat dintr-un text târziu al lui Louis Althusser, în care filosoful francez distinge între un “materialist aleatoriu” și un materialist “dialectic,” care apare în Prefața cărții. Dimensiunea critică a proiectului lui Iovănel a fost deja discutată într-o serie de articole și mă ocup de aceasta în ultima parte a acestui eseu. Despre dimensiunea literară a proiectului său s-a vorbit mai puțin. Aș dori să evaluez, dintr-un punct de vedere mărturisit marginal, calitățile și defectele Istoriei în măsura în care acestea rezultă din articularea celor două dimensiuni amintite. Cuvinte-cheie: Mihai Iovănel, poetica istoriei literare, materialism aleatoriu, literatura română contemporană